PENGARUH BAURAN PEMASARAN TERHADAP DAYA SAING INDUSTRI KERAJINAN TEMBAGA (Studi Kasus Pada Pengrajin Di Desa Tumang Kecamatan Cepogo Kabupaten Boyolali) - Hanifah Millatina; NUNING LISDIANA; HARI PURWANTO (Universitas Boyolali, 2020)
ABSTRACT The problem in this study is the increasing competition in the world of copper handicraft industries in Tumang Village, Cepogo District, Boyolali Regency both in the fields of production and marketing. This is evident in the increasingly fierce competition lately. The purpose of this study is to find out how the marketing mix (product, price, place and promotion) influences the competitiveness of the copper industry. In this study, the subjects of the study were the craftsmen of the copper handicraft industry in Tumang Village, Cepogo District, Boyolali Regency. A sample of 50 craftsmen. The method used in this study is explanatory survey, namely by using a questionnaire as a means of data collection and data analysis techniques using multiple linear regression. Partial results of the product variable, price and place do not significantly influence competitiveness. While the promotion variable has a significant positive effect on competitiveness. And simultaneously showing product, price, place and promotion variables have no significant effect on competitiveness. Keywords: marketing mix, product, price, place, promotion, competitiveness